Evaluation of antidepressant activity of l-methylfolate per se and its interaction with escitalopram in mice - More, Sapna A.; Mishra, Pooja S.; Tiwari, Ashutosh; Vyas, Savita (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Depression is a worldwide illness in the current population. Low levels of L-methylfolate are linked to depression. Present study evaluates the anti-depressive activity of acute and chronic administration of L-methylfolate per se in forced swimming test (FST) and tail suspension test (TST) and its interaction with escitalopram in albino mice. Methods: For this 30 swiss albino mice were divided randomly into five groups (n=6) as group I (control,10ml/Kg, p.o) - 2% suspension of gum acacia, group II - escitalopram suspension (10mg/kg, p.o), group III- L-methylfolate suspension (3mg/kg, p.o), group IV- L-methylfolate (3mg/kg, p.o) plus escitalopram (5mg/kg, p.o), group V- L-methylfolate(3mg/kg, p.o) plus escitalopram(10mg/kg, p.o), for forced swimming test. In tail suspension test again, mice were divided in five groups as above except that the dose of L-methylfolate was reduced to 1.25mg/kg. The pharmacologically validated models forced swimming test and tail suspension test were performed in mice to evaluate acute and chronic antidepressant activity of L-methylfolate and its combination with escitalopram respectively, after performing an acute toxicity study. Results: L-methylfolate and L-methylfolate plus escitalopram (10mg/Kg and 5mg/Kg, p.o) showed acute and chronic antidepressant activity in albino mice in FST and TST respectively. In human L-methylfolate is only active form of folic acid that readily crosses the blood brain barrier and utilized by the CNS. It regulates the bioavailability of critical cofactor BH4, required by enzymes synthesizing monoamines whose deficiency leads to depression. Conclusions: Hence, this study suggests antidepresant activity of L-methylfolate per se and as adjuvant with escitalopram when initiated from initiation of antidepressant therapy. Also, L-methylfolate opens the possibility of reducing the dose of antidepressant when used as adjuvant.